2021
DOI: 10.3390/ani11040968
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Local Tissue Reactions after Anti-GnRF Injection in Male Pigs Assessed Using Magnetic Resonance Imaging

Abstract: This study aimed at evaluating the local tissue reaction of an anti-GnRF product, which is used for the so called “immunocastration” in male pigs. A total of 34 pigs were injected two times (including a booster injection) with an anti-GnRF product. Injection was performed using the prescribed safety vaccinator. Injection sites were evaluated three times post injection using magnetic resonance imaging. Two examinations were performed after the first injection and one after the booster. The local tissue reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Human and animal research [ 16 , 17 , 18 , 19 , 26 , 27 ] have shown that the optimum injection depth results in less pain and being transferred to animals might result in higher animal welfare. This is of great importance, even if irritating inoculums or vaccines are used, which can result in large-scale tissue alterations [ 1 , 2 , 5 , 6 , 7 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human and animal research [ 16 , 17 , 18 , 19 , 26 , 27 ] have shown that the optimum injection depth results in less pain and being transferred to animals might result in higher animal welfare. This is of great importance, even if irritating inoculums or vaccines are used, which can result in large-scale tissue alterations [ 1 , 2 , 5 , 6 , 7 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the volume of injectable solutions may influence the location and the local reaction [ 1 , 2 , 5 , 25 ]. Therefore, muscle growth should be taken into account as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, MRI in pigs is mainly being used for research purposes-and not for classical performance testing [39][40][41][42][43][44]. A few studies exist, however, where MRI (+DXA) helped to verify or to develop new performance test equations related to fattening of intact boars [45] or to test relationships between male phenotypes and carcass and meat quality [46,47], as was also done by using CT [48].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Further useful applications of MRI include the determination of in vivo tissue aberrations (density and volume changes) after the administration of different vaccines or hormone analogs in pigs [40,49,50]. The administration of a GnRF analog can lead to massive tissue changes and ultimately tissue necrosis at the administration site [40,50], negatively affecting muscle function and local meat quality.…”
Section: Principle Of Magnetic Resonance Imaging: the Body Part Of Interest Is Positioned In The Center Of The Magnetic Field While A Bodmentioning
confidence: 99%